Vacant Land on Southside of Tulare Street Between 1st and 6th Streets - Watkins, Howard::::::::: (1983)
Southeast corner of Tulare and First Streets with Coldwell Banker signage; December 1983 opening for retail space Pallets of cement blocks in background